2004
DOI: 10.1113/jphysiol.2003.057729
|View full text |Cite
|
Sign up to set email alerts
|

The control of ventilation is dissociated from locomotion during walking in sheep

Abstract: This study was designed to test the hypothesis that the frequency response of the systems controlling the motor activity of breathing and walking in quadrupeds is compatible with the idea that supra-spinal locomotor centres could proportionally drive locomotion and ventilation. The locomotor and the breath-by-breath ventilatory and gas exchange (CO 2 output (V CO 2 ) and O 2 uptake (V O 2 )) responses were studied in five sheep spontaneously walking on a treadmill. The speed of the treadmill was changed in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…20). In other words, when conditions are created where work rate changes with no concurrent change inV O 2 andV CO 2 ,V E follows factors related to gas exchange rate and not to the motor activity (151,154).…”
Section: Caveats With Neural Feed Forward and Feedback Hypotheses Of mentioning
confidence: 99%
“…20). In other words, when conditions are created where work rate changes with no concurrent change inV O 2 andV CO 2 ,V E follows factors related to gas exchange rate and not to the motor activity (151,154).…”
Section: Caveats With Neural Feed Forward and Feedback Hypotheses Of mentioning
confidence: 99%
“… Δ versus Δ relationship for all the tests (•) when c P a,CO 2 was maintained constant The open symbols are mean values from previous studies from our laboratory: □, mean value obtained in spontaneously walking sheep (Haouzi et al 2004 a ); ○, mean value obtained during ERC in the sheep, but with an ‘intact’ cephalic circulation (Haouzi et al 1997). …”
mentioning
confidence: 99%
“…Haouzi et al . [16] also reported that parallel adjustments of the locomotor activity and V̇ E were observed during treadmill walking in the sheep. Wells et al .…”
Section: Discussionmentioning
confidence: 98%
“…Second, following 5 min of walking at constant speed at the midpoint of the sinusoidal walking speed (4.5 km·h -1 ), the treadmill speed was changed with a sinusoidal pattern from 3 km·h -1 to 6 km·h -1 at a period ( T ) of 10, 5, 2 and 1 min and in a stepwise manner (steady-state) at the speeds of 3 km·h -1 and 6 km·h -1 for each 5 min [4,16–18]. The sinusoidal loading was repeated for five cycles at 1 min periods and continued three cycles at 2 min periods following warming up at a constant work load at the midpoint between the maximum and minimum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation